CC-006 Eosinophilicophilic gastritis due to carbimazole therapy presenting with a history and investigations mimicking gastric carcinoma. (23rd September 2015) - Patel, S; Fleming, A; Reffitt, D
Abstract : Introduction: An 82-year-old woman was referred for investigation of a 6-month history of anorexia, progressive weight loss and epigastric discomfort. Methods: She had a history of hyperthyroidism diagnosed 7 months previously. Currently, she was euthyroid on carbimazole. Results: On examination there was a palpable tender mass in the left upper quadrant. Abdominal ultrasound demonstrated an irregular mass and CT scan gross gastric wall thickening and lymphadenopathy suggesting probable gastric malignancy. An OGD confirmed an ulcerated mass in the posterior wall, however, biopsies failed to confirm malignancy and therefore treatment was commenced with Lanzoprazole. Subsequent OGD showed persistence of the mass. Repeat histology showed no evidence of malignancy but demonstrated an inflammatory cell infiltrate within the gastric mucosa with a predominance of eosinophils. Review of the previous biopsy confirmed a similar eosinophilic infiltrate was present. A diagnosis of eosinophilic gastritis rather than malignancy was made. As both biopsies demonstrated eosinophils we reviewed her medication. The literature reports one case of carbimazole induced eosinophilic granulomatous vasculitis localised to the stomach presenting similarly but no cases of eosinophilic gastritis.1 Hence, we hypothesised that carbimazole may be aetiological here and the drug was discontinued. In view of her significant weight loss and anorexia a reducing course of prednisolone was simultaneously commenced. Over the next 6 weeks, there was an improvement in the patient's clinical condition: her appetite returned and she regained the weight loss. She remained well after discontinuing the prednisolone with no recurrence. Subsequent CT scan demonstrated no evidence of the previous mass or lymphadenopathy and a repeat gastroscopy demonstrated no mucosal thickening or ulceration. Conclusion: Eosinophilic gastritis is a rare condition that usually presents between the second and th decades of life.2 The mainstay of treatment is corticosteroids. Our patient was treated with a short course of prednisolone and withdrawal of carbimazole. She remained symptom free off carbimazole with no recurrence suggesting that carbimazole was the cause of the Eosinophilic Gastritis. This is the first reported case of Eosinophilic Gastritis due to carbimazole therapy. The clinical presentation, endoscopic and histological findings mimic the presentation of gastric cancer and highlight the importance of histological confirmation in the diagnosis of gastric cancer.